Variability in along-shelf and cross-shelf circulation in the South Atlantic Bight. (15th February 2017) - Yuan, Yeping; Castelao, Renato M.; He, Ruoying
Abstract: Variability in along-shelf and cross-shelf circulation in the South Atlantic Bight (SAB) is investigated using altimetry observations. Satellite-derived along-shelf velocity anomalies are in good agreement with independent near-surface current measurements from moored acoustic Doppler current profilers and surface velocities from high frequency radar at adjacent locations. This is especially true if wind-driven Ekman velocities are added to the geostrophic velocities, suggesting that the influence of Ekman dynamics to surface along-shelf flow in the SAB is unusually large. The decade-long time series reveals substantial seasonal variability in surface velocities, with peak poleward anomalies during late spring and summer and strong equatorward flow during autumn. Convergences and divergences in the along-shelf transport between two cross-sections are compared with three-dimensional numerical model results and used to estimate cross-shelf transport across the 50 m isobath in the SAB. The calculation suggests a pattern of weak offshore flow during spring followed by prolonged and relatively stronger offshore flow during summer and early autumn, while cross-shelf velocity anomalies during winter are weak and slightly onshore. Prolonged offshore flow following the peak in river discharge that generally occurs in spring indicates the potential for the establishment of a conduit for offshore export of riverine material. The long-term time series also reveals several large events of interannual variability, including the 2003 cold event observed in the SAB. Abstract : Highlights: Long-term along-shelf and cross-shelf circulation was investigated in the South Atlantic Bight. Along-shelf circulation is characterized by strong seasonality. Increased offshore flow is observed during summer following peak in river discharge.